Protective effect of Ginkgo biloba extract on CCI4-induced liver damage - Bahçecioglu, IH; Ustundag, B; Ozercan, I; Erçel, E; Baydas, G; Akdere, T; Demir, A (Elsevier Sci Ireland Ltd, 1999)
In this study, the protective effect of Ginkgo biloba extract (EGb 761), an antioxidant, on carbon tetrachloride (CCl4)-induced liver damage were investigated in rats. Malondialdehyde (MDA, a breakdown product of lipid peroxidation) levels, histopathological findings and serum enzyme activities were evaluated. Rats were divided into two groups: The first group (CCl4 plus EGb 761) was composed of 18 rats, whereas the second group (CCl4) had 14 rats. A total of 0.15 ml/100 g body weight CCl4 were injected subcutaneously for 3 days/week to the rats in both groups. In the first group, 200 mg/kg per day EGb 761 were added to drinking water. The second group of rats received only tap water. After the 4-week treatment, rats were sacrificed, blood samples were collected for determination of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase ALP), and plasma MDA levels. Liver tissue samples were used for histopathological examinations and measurement of MDA levels. Plasma MDA levels, ALT, AST and ALP activities were significantly higher in CCl4 group compared to the CCl4 plus EGb 761 group (P < 0.05, P < 0.01, P < 0.01, P < 0.05, respectively). The level of liver MDA was significantly decreased in the CCl4 plus EGb 761 group than CCl4 group (P < 0.001). In histopathological examination, fatty degeneration and fibrosis were found to be significantly decreased in the CCl4 plus EGb 761 group (P < 0.01). In conclusion, EGb 761 may be effective in arresting the development of liver fibrosis and fatty degeneration in oxidative liver damage by reducing the formation of lipid peroxidation. (C) 1999 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: Ginkgo biloba extract; malondialdehyde; carbon tetrachloride; oxidative liver damage